Black cultural traffic : crossroads in global performance and popular culture (Book collections on Project MUSE., 2005)
"Black Cultural Traffic traces how blackness travels globally in performance, engaging the work of an international and interdisciplinary mix of scholars, critics, and practicing artists. The book's essays provide nuanced and complex perspectives on black culture--not as a static set of shared beliefs and customs but as something that is contingent and dynamic. The essays engage with critical issues such as circulation, cultural appropriation, commodification, commercialization, and hybridity as they take up subjects that include television, hip-hop, R&B, gospel, film, theater, fashion, and pop music celebrities in Africa, Europe, and the United States. The book's engaging combination of scholarship with artists' statements will appeal to anyone interested in understanding the circulation and multidirectional movements of black culture"--Publisher's description.